Solubility and preferential solvation of meloxicam in methanol + water mixtures at 298.15 K (2014)
The equilibrium solubility of meloxicam in methanol + water binary mixtures at 298.15 K was determined and the preferential solvation parameters were derived from their thermodynamic solution properties by means of the inverse Kirkwood–Buff.